Binge drinking among young adults in an urban tertiary care emergency department in Israel - Daphna Levinson; Paola Rosca; Doron Vilner; Idit Brimberg; Yael Stall; Ayelet Rimon (BMC, 2017)
Abstract Background Alcohol use is a major preventable public health problem with serious health and social consequences especially among youth. In Israel, alcohol use has become an emerging problem during the last decade, and its use has increased among adolescents and young adults. Binge drinking is the common pattern of alcohol consumption among young adults who drink for recreational purposes. The present survey was conducted among 16-35 years old visitors to the ED. The aim was specifically to identify binge drinkers in order to assess the scope of the need for a brief counseling intervention among young people who arrive intoxicated to a large tertiary care urban ED in Israel. Methods The survey was conducted throughout a 1 week period (24 h per day) at the general EDs in a large, tertiary care center, situated in Tel Aviv. During the survey week, 946 individuals, aged 16-35, visited the ED and 573 (63%) of them were approached for an interview. 89% of those approached agreed to be interviewed. Consenting patients [N = 348] were asked whether they drink any alcohol, how often they drink and how much. Results About one fifth of those interviewed were in the habit of consuming more than four units of alcohol per occasion. Drinking several times a week or every day was reported by 19% of the males and 26% of the females. Frequency of the drinking episodes was highly correlated with the number of units of drink per occasion. Conclusions The study found a very high rate of binge drinking among ED visitors, and this suggests a need for large scale ED-based interventions. As binge drinkers are at elevated risk for accidents, violence and related problems, effective ED-based interventions could make an important contribution to public health. Accordingly, Israel is in the process of assessing the effectiveness of a large-scale ED-based counseling intervention. Trial registration Trial registration number 0230-13-TLV.